Different impacts of manure and chemical fertilizers on bacterial community structure and antibiotic resistance genes in arable soils. (December 2017) - Liu, Peng; Jia, Shuyu; He, Xiwei; Zhang, Xuxiang; Ye, Lin
Abstract: Both manure and chemical fertilizers are widely used in modern agriculture. However, the impacts of different fertilizers on bacterial community structure and antibiotic resistance genes (ARGs) in arable soils still remain unclear. In this study, high-throughput sequencing and quantitative PCR were employed to investigate the bacterial community structure, ARGs and mobile genetic elements (MGEs) influenced by the application of different fertilizers, including chemical fertilizers, piggery manure and straw ash. The results showed that the application of fertilizers could significantly change the soil bacterial community and the abundance of Gaiella under phylum Actinobacteria was significantly reduced from 12.9% in unfertilized soil to 4.1%–7.4% in fertilized soil ( P < 0.05). It was also found that the application of manure could cause a transient effect on soil resistome composition and the relative abundance of ARGs increased from 7.37 ppm to 32.10 ppm. The abundance of aminoglycoside, sulfonamide and tetracycline resistance genes greatly increased after manure fertilization and then gradually returned to normal levels with the decay of some intestinal bacteria carrying ARGs. In contrast, the application of chemical fertilizers and straw ash significantly changed the bacterial community structure but exerted little effect on soil resistome. Overall, the results of this study illustrated the different effects of different fertilizers on the soil resistome and revealed that the changes of soil resistome induced by manure application mainly resulted from alteration of bacteria community rather than the horizontal gene transfer. Highlights: The impacts of fertilizers on soil bacterial community and ARGs were investigated. Fertilizers could change the soil bacterial community by changing soil properties. Manure fertilizer could cause transient effects on soil ARG composition. Some ARGs increased after manure fertilization then gradually decreased.